Vulnerability to Unsafe Sex and HIV Infection Among Wives of Migrant Workers in Far Western Nepal - Aryal, Arjun; Yogi, YN; Ghimire, H (Journal of Chitwan Medical College, 2013)
In average, one from every two households of Far-Western Nepal, and 14.75 % of the male population of Dadeldhura, Doti and Kailali were at abroad, mostly in India. The migrant people engage in high risk sexual practices in India, contract Human Immuno-deficiency Virus (HIV) and transmit it to their wives. The prevalence of HIV among wives of migrants as per Integrated Biological and Behavioral Surveillance Survey (2008) was 3.3%. So, it was important to study the HIV related knowledge and vulnerability of these women. The study was carried out in 297 randomly selected wives of migrant workers in Doti, Dadeldhura and Kailali districts of Nepal. Eighty-six percent of the respondents had heard of HIV and AIDS, 4% had comprehensive knowledge on HIV prevention; 64% perceived HIV could transmit through mosquito bite and 42% of the women knew at least two advantages of condom. The women ever discussed about sex with their husbands were 34%. Seventy two percent expressed that People Living with HIV would not reveal their HIV status due to fear of losing social respect associated with discrimination. Comprehensive education program is needed to increase the level of correct knowledge on HIV prevention among wives of migrant workers. Targeted intervention among wives of migrant workers is important to make them able to negotiate for safe sexual practices with their husbands for HIV prevention and disclose their status for accessing services. Journal of Chitwan Medical College 2013; 3(1): 26-31 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8462